Monthly Motivational Interview Counseling and Nicotine Replacement Therapy for Smoking Parents of Pediatric Patients: A Randomized Controlled Trial - Dai, Siyu; Chan, Michael Ho Ming; Kam, Richard Kin Ting; Li, Albert Martin; Au, Chun Ting; Chan, Kate Ching-Ching (Frontiers in Pediatrics, 2022)
Background: Parental smoking is the dominate source of passive smoke exposure in pediatric population. The current RCT study aimed to evaluate the effectiveness of a multi-component smoking reduction intervention in parental smoking reduction and children’s environmental tobacco smoke exposure reduction in clinical settings. Methods: A single-blinded, 6-month randomized controlled trial recruited smoking parents (N=210) of children who attended the pediatric wards or clinics at Prince of Wales Hospital. Participants allocated to the intervention group (n=105) received monthly motivational interviews on smoking reduction with emphasis on health hazards related to children’s passive smoke exposure, 8-week nicotine replacement therapy and referral to smoking cessation service if the parents preferred. Control group (n=105) received simple verbal advice on smoking cessation. Primary outcomes were parental urine cotinine-validated and self-reported ≥50% smoking reduction rates at 6-month. Results: Smoking parents in the intervention group had significantly more biochemically validated ≥50% smoking reduction than the control: 27.1% vs. 10.0%, (OR=3.34, 95% CI: 1.16-9.62, P=0.02). Rate of self-reported ≥50% smoking reduction was also significantly higher in the intervention group than the control: 51.9% vs. 20.2%, (OR=4.40, 95% CI: 2.38-8.12, P<0.001). For secondary outcomes, rate of parental self-reported smoking cessation was higher in the intervention arm: 10.5% vs. 1.0%, (OR=12.17, 95% CI: 1.54-96.07, P<0.001), however, no differences were detected in biochemically validated cessation and changes in children’s passive smoke exposure between groups. Conclusions: Monthly smoking reduction counselling together with nicotine replacement therapy is more effective than simple verbal cessation advice in smoking reduction for parents of pediatric patients. However, our study did not demonstrate differences in smoking cessation or reduction in children passive smoke exposure with a 6-month follow up. Achievement of smoke-free environment remains challenging.